Reflecting on the COVID-19 crisis and lessons learn for a better future - Alkhawaldeh, Qusai; Muğan, Güliz (Journal of Risk and Crisis Management, 2022)
The growing COVID-19 pandemic has become a global emergency. At the time of writing, it has resulted in more than 510 million confirmed illnesses and 6 million deaths, as well as unparalleled preventative measures that have imprisoned a significant percentage of the worldwide population and established social separation as a new global behavioral norm. The COVID-19 dilemma has had a significant influence on all elements of daily life and work, as well as the global economy. Reflecting on the current crisis's issues and the lessons we may learn from them include: (i) increased phenomena and the early warnings, (ii) social and spatial disparity, and (iii) prevention is less expensive than treatment.
Keywords: Coronavirus; Crisis; Social and spatial disparity